Benefits of self-etch adhesives active application with rotary brush to enamel - Ayar, Muhammet Kerim (Vojnosanitetski pregled, 2021)
Background/Aim. Theoretically, agitation of self-etch adhesive and solutions can be significantly accelerated by the use of the rotary brush. The aim of this study was to evaluate application of a universal adhesive in a self-etch mode and a self-etch adhesive using a rotary brush active application technique by microshear bond strength (µSBS) test. Methods. The crown parts of 20 bovine teeth were separated from their roots, embedded in acrylic blocks and enamel surfaces were prepared. The prepared crowns were divided into four groups according to the adhesive system tested (Nova Compo-B Plus, and Optibond All-in-one), and application technique (manual active application and rotary brush active application). Bonded samples were immersed in distilled water for 24 h before bond strength testing by µSBS test at 1.0 mm/min. Data were analyzed using non-parametric tests (p = 0.05). Results. Both adhesives, applied by rotary brush active application technique, showed significantly higher enamel bonding strength compared to the manual active application technique. Conclusion. Application of self-etch adhesives to enamel with a rotary brush active application technique can significantly increase initial resin-enamel bond strength compared to the manual active application.